Resale Product and Accessory Opportunities for Audiology Practices - Bankaitis Smith, A. U. (Seminars in Hearing, 2019)
Patients need and/or want access to any number of products, including consumables and durable goods, and accessories as part of their audiology care. Audiologists have an opportunity to offer products and accessories for resale from their clinical office. Several methods for reselling items to established patients including an overview of an ecommerce approach successfully implemented by several individual audiology private practices will be reviewed. Upon completion, readers will be familiar with the general steps for incorporating an e-shop within an existing business Web site. Additionally, insights as to effective tactics for generating e-shop revenue will be shared.
Keywords: ecommerce; resale product; resale accessory; consumables; durable goods; e-shop